Matrix-assisted laser desorption ionization time-of-flight mass spectrometry for rapid identification of mold and yeast cultures of Penicillium marneffei. Issue 1 (December 2016) - Lau, Susanna; Lam, Clare; Ngan, Antonio; Chow, Wang-Ngai; Wu, Alan; Tsang, Dominic; Tse, Cindy; Que, Tak-Lun; Tang, Bone; Woo, Patrick
Abstract Background Penicillium marneffei is the most important thermal dimorphic fungus causing systemic mycosis in HIV-infected and other immunocompromised patients in Southeast Asia. However, laboratory diagnosis of penicilliosis, which relies on microscopic morphology and mycelial-to-yeast conversion, is time-consuming and expertise-dependent, thus delaying diagnosis and treatment. Although matrix -assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) is useful for identification of various medically important fungi, its performance for identification ofP. marneffei is less clear. Results We evaluated the performance of the Bruker MALDI-TOF MS system for identification of mold and yeast cultures of 59 clinical strains and the type strain ofP. marneffei using the direct transfer method, with results compared to four phylogenetically closely related species, P. brevi-compactum, P. chrysogenum, Talaromyces aurantiacus andT. stipitatus . Using the Bruker original database combined with BDAL v4.0.0.1 and Filamentous Fungi Library 1.0, MALDI-TOF MS failed to identify the 60P. marneffei strains grown in mold and yeast phase (identified asP. funiculosum andP. purpurogenum with scores <1.7 respectively). However, when the combined database was expanded with inclusion of spectra from 21P. marneffei strains in mold and/or yeast phase, all the remaining 39P. marneffei strains grown in mold or phase were correctly identified to the species level with score >2.0. The MS spectra ofP. marneffei exhibited significant difference to those ofP. brevi-compactum, P. chrysogenum, T. aurantiacus andT. stipitatus . However, MALDI-TOF MS failed to identify these four fungi to the species level using the combined database with or without spectra fromP. marneffei . Conclusions MALDI-TOF MS is useful for rapid identification of both yeast and mold cultures ofP. marneffei and differentiation from related species. However, accurate identification to the species level requires database expansion usingP. marneffei strains.